2017
DOI: 10.20944/preprints201706.0032.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modifications of Porphyrins and Hydroporphyrins for their Solubilization in Aqueous Media

Abstract: Abstract:The increasing popularity of porphyrins and hydroporphyrins for application in a variety of biomedical (photodynamic therapy, fluorescence tagging and imaging, photoacoustic imaging) and technical (chemosensing, catalysis, light harvesting) applications is also associated with the growing number of methodologies that enable their solubilization in aqueous media. Natively, the vast majority of synthetic porphyrinic compounds are not water-soluble. Moreover, any water-solubility imposes several restrict… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…(Fig. 51 ) . A multifold contrast enhancement in PA amplitude was reported in comparison with the ICG dye attributed to a short triplet lifetimes, low fluorescence quantum yield.…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 83%
See 1 more Smart Citation
“…(Fig. 51 ) . A multifold contrast enhancement in PA amplitude was reported in comparison with the ICG dye attributed to a short triplet lifetimes, low fluorescence quantum yield.…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 83%
“…Structure of the water‐soluble NIR absorbing tetra‐ PEG ‐ylated quinolone‐annulated porphyrin 51 reported by Luciano et al . .…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 99%
“…While several phenyl- and substituted phenyl-derivatives were reported [ 3 , 4 ], the by far most popular derivative is the meso -tetrakis(pentafluorophenyl)porpholactone (T F PL) and its metal complexes (T F PLM) [ 1 , 5 , 6 ]. This is because of their relative ease of synthesis in one step from T F PP using a number of different methodologies (see below Scheme 2 ) and the multiple possibilities to derivatize the C 6 F 5 -groups by means of nucleophilic aromatic substitution reactions to, for example, render them water-soluble [ 6 , 7 , 8 ]. The presence of a ß,ß’-lactone moiety in carbaporphyrins [ 9 ], thiaporphyrins [ 10 , 11 ], octaalkylporphyrins [ 12 ], or subporphyrins [ 13 ] is known but much more rare and the utility of these compounds has not yet been shown.…”
Section: Introductionmentioning
confidence: 99%
“… 20 28 A number of these applications, especially in the biomedical sphere, require water-soluble derivatives of the complexes, which are typically accessible via cumbersome synthetic and purification steps. 2 , 29 , 30 A recent reinvestigation of iridium corroles (in which 4-picolinic acid derivatives were found to be partially water-soluble) suggested that the use of water-soluble axial ligands might afford a simple, one-pot route to water-soluble Ir corroles as a new class of singlet oxygen photosensitizers. 31 The beguilingly simple exercise, however, threw up unexpected challenges.…”
Section: Introductionmentioning
confidence: 99%